2005
DOI: 10.1080/10691898.2005.11910567
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Students to Use Summary Statistics and Graphics to Clean and Analyze Data

Abstract: Textbooks and websites today abound with real data. One neglected issue is that statistical investigations often require a good deal of "cleaning" to ready data for analysis. The purpose of this dataset and exercise is to teach students to use exploratory tools to identify erroneous observations. This article discusses the merits of such an exercise and provides a team project, problem data, cleaned data for instructors, and reflections on past experiences. The main goal is to give instructors a prepared proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The influx of data and advances in computing have led to calls by several statisticians to update the introductory statistics curriculum to provide students with the computational tools and data-related capacity imperative for modern practice (e.g., Horton et al, 2014;Nolan & Temple Lang, 2010). Some instructors have already begun integrating more data and computational practices into the introductory course, including relational databases (e.g., Broatch et al, 2019), web scraping (e.g., Dogucu & Cetinkaya-Rundel, 2021), data wrangling (e.g., Hardin, 2018;McNamara & Horton, 2018), data cleaning (Holcomb & Spalsbury;2005), multivariate visualization (e.g., Çetinkaya-Rundel & Tackett, 2020;Kaplan, 2018), reproducibility (e.g., Baumer et al, 2014), and version control tools (Beckman et al, 2021;Fiksel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The influx of data and advances in computing have led to calls by several statisticians to update the introductory statistics curriculum to provide students with the computational tools and data-related capacity imperative for modern practice (e.g., Horton et al, 2014;Nolan & Temple Lang, 2010). Some instructors have already begun integrating more data and computational practices into the introductory course, including relational databases (e.g., Broatch et al, 2019), web scraping (e.g., Dogucu & Cetinkaya-Rundel, 2021), data wrangling (e.g., Hardin, 2018;McNamara & Horton, 2018), data cleaning (Holcomb & Spalsbury;2005), multivariate visualization (e.g., Çetinkaya-Rundel & Tackett, 2020;Kaplan, 2018), reproducibility (e.g., Baumer et al, 2014), and version control tools (Beckman et al, 2021;Fiksel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Other research focussed on cooperative learning of statistics, which has been shown to have beneficial effects on student learning (Garfield, 1993;Giraud, 1997;Magel, 1998). Recommendations are primarily given for lectures (e.g., Larsen, 2006), methods for teaching specific subjects (e.g., Walters, Morrell & Auer, 2006), the use of data sets (e.g., Holcomb & Spalsbury, 2005), textbooks (e.g., von Hippel, 2005), and specific exercises (e.g., Kahn, 2005).…”
Section: Improving Educationmentioning
confidence: 99%